IMPLEMENTASI KAIDAHLA YUNKIRU TAGAYYUR AL-AHKAM BITAGAYYUR AL-AZMAN WA AL-AHWAL DALAM IBADAH DI MASA PANDEMI - Kumaidi, Muhamad; Febriani, Evi (Universitas Islam Negeri Raden Intan Lampung, 2020)
Covid 19, which spread on the earth, changed the whole social order, be it economics, education, politics, health and even the way of Muslims, especially worship. This is caused by an emergency requiring everyone not to carry out activities outside the home, so that the impact on all worship activities that should be carried out by worshiping in the mosque must be avoided. In this article the author tries to explore changes in law if viewed from the side of the rule “La Yunkiru Tagayyur Al-Ahkam Bitagayyur Al-Azman wa Al-Ahwal” (not denied the change in a law due to the eruption of the times and circumstances) during a pandemic. This principle becomes the basis of the flexibility of Islamic law in accordance with the development and conditions of the times. So that Islamic law is always present as a law in accordance with human history throughout the ages from the time of Adam to the end of time. Islam is always suitable and in accordance with all climates and all nations throughout the world. It is a religion that remains perfect when faced with all the changes that are continually there. Islam comes with ease and flexibility, not a religion that has not been stagnant when responding to changing timesKey words: Covid 19, Islamic Law, Changing Times Covid 19 yang merebak di bumi merubah tatanan bermasyarakat seluruhnya, baik ekonomi, pendidikan, politik, kesehatan bahkan cara umat Islam beragama khususnya ibadah. Ini oleh akibatkan olehkondisi darurat menuntut setiap orang untuk tidak melakukan aktivitas di luar rumah, sehingga berdampak pada seluruh aktivitas ibadah yang harusnya dilaksanakan dengan caraberjamaah di masjid harus dihindari.Dalam artikel ini penulis mencoba menggali perubahan hukum jika ditinjau dari sisi kaidah “La Yunkiru Tagayyur Al-Ahkam Bitagayyur Al-Azman wa Al-Ahwal”(tidak diingkari berubahnya sebuah hukum disebabkan karena berubanhya zaman dan keadaan) di masa pandemi.Kaidah ini menjadi dasar fleksibelitas syariat Islam yang sesuai dengan perkembangan dan keadaan zaman.Sehingga syariat Islam selalu hadir sebagai syariat yang sesuai dengan sejarah manusia sepanjangzaman sejak masaNabi Adam hingga manusia akhir zaman.Islam selalu cocok dan sesuai dengan segala iklim dan segala bangsa di seluruh dunia.Ia agama yang tetap sempurna ketika dihadapkan pada segala perubahan yang terus menerus ada. Islam datang dengan kemudahan dan keluwesan bukan agama yang jumud (stagnan) tidak bisa berkembang saat merespon perubahan keadaan zaman.Key words:Covid 19, Hukum Islam, Perubahan Zaman",